Complexidade estrutural e diversidade de macrófitas aquáticas influenciam padrões de diversidade das aranhas em ambientes alagados naturais e em ambientes antropicamente alterados sob invasão biológica. - Silva, Emanuel Giovani Cafôfo (2018)
The niche of a species is linked to all resources that its individuals need, such as structural complexity for example. Species of spiders, for example, interact with the structural complexity of the plants in which they live. In this sense, macrophytes would be habitats and their structural complexity micro-habitats. Many organisms that live on these plants are affected by their habitats and micro-habitats features. Under this scope, two approaches were analyzed: (I) investigate whether the number of plant species and their structural complexity affect spider diversity, such as species and individuals density; (II) to compare the complexity between one invasive species and a native one by doing the same comparinson with the spider assemblages that live on these plants. To test the first approach (I) spiders were sampled in 37 sample units (UA) of 1 m², considering a physical structure spectrum (horizontal and vertical complexities and height of vegetation) and diversity of macrophyte species (Shannon index) on a coarse spatial scale on the the Upper Paraná River floodplain. The results suggest that species and individuals densitys of spiders that inhabit macrophytes are influenced by the availability of micro-habitats, and the distinction of habitat was important because it increased the abundance of organisms. In the second approach (II) spiders were sampled and measures of habitat complexity were made in macrophyte patches dominated by the invasive U. arrecta (25 UA1 m²) and by the native macrophyte Eichhornia azurea (25 UA1 m²). The results indicated that U. arrecta changes the patterns of natural composition, leading to the loss of some water related spiders. All these finds raises many other relevant ecological questions about habitat complexity, diversity and invasion dynamics. Besides this, these results are very relevant to expand the knowledge about the factors that drives spiders diversity on wetlands, and how invasion process interacts with these dynamics.